Big Five Audits and Accounting Fraud* - LENNOX, CLIVE; PITTMAN, JEFFREY A. (Contemporary Accounting Research, 2010)
All in-text references underlined in blue are linked to publications on ResearchGate, letting you access and read them immediately.